2008
DOI: 10.4049/jimmunol.181.5.3057
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Affect Dendritic Cell (DC) Potassium Channel Function and Modulate DC T Cell Stimulatory Capacity

Abstract: Cannabinoids affect diverse biological processes, including functions of the immune system. With respect to the immune system, anti-inflammatory and immunosuppressive effects of cannabinoids have been reported. Cannabinoids stimulate G protein-coupled cannabinoid receptors CB1 and CB2. These receptors are found primarily on neurons. However, they are also found on dendritic cells (DC), which are recognized for their critical role in initiating and maintaining immune responses. Therefore, DC are potential targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…These findings were consistent with other studies that have shown A -induced I A activation [81,82]. In contrast, CB1 receptor activation has been demonstrated to attenuate the voltage-activated K + currents [83,84].…”
Section: Discussionsupporting
confidence: 83%
“…These findings were consistent with other studies that have shown A -induced I A activation [81,82]. In contrast, CB1 receptor activation has been demonstrated to attenuate the voltage-activated K + currents [83,84].…”
Section: Discussionsupporting
confidence: 83%
“…15 -17 Cannabinoids reduce the MHC class II expression on the surface of dendritic cells, hence affecting antigen presentation, and inhibit peripheral T-cell activation in response to lipopolysaccharide and anti-CD3 antibodies. 26,29,30 Based on these findings, several studies have focused on the use of cannabinoids for the treatment of immune-mediated diseases, both in experimental models and humans. 29 As the dysregulated proinflammatory response observed in IBD pathogenesis is characterized by a T helper cell type (Th)1 / Th17 immune profile, 31 we explored the influence of endocannabinoids on T cell-mediated gut inflammation, by investigating the in vitro and ex vivo effects of the synthetic non-hydrolysable AEA analog MAEA on proinflammatory cytokine production by anti-CD3 / CD28-stimulated LPMCs, CD3 + LPMCs, and biopsies from inflamed IBD mucosa.…”
Section: Articlesmentioning
confidence: 99%
“…MHC molecules are particularly induced upon cell maturation and activation by specific transactivators, the most important of which is MHC class II transactivator CIITA (Reith et al 2005). Very few reports have investigated the role of phyCBs and syCBs on the regulation of MHC expression, yet there is a general consensus that these compounds may reduce MHC molecules either directly (Wacnik et al 2008) or through downregulation of CIITA (Gongora et al 2004). …”
Section: Cannabinoid-mediated Integration Of Brain Immunitymentioning
confidence: 98%